THE LIFE AND STATECRAFT OF AMIR TEMUR IN JEAN BODIN'S INTERPRETATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
In this article, the work of the French orientalist Jean Bodin, who commented on the life and statecraft of Amir Temur in the 16th century, is analyzed. In the early 16th century, the strengthening of the Habsburg dynasty in Germany posed a serious threat to both France and the Ottoman Empire. As a result, diplomatic relations emerged between the two states. French diplomats began visiting Constantinople from the 1530s onward. During these diplomatic missions, the envoys were impressed by the policy of tolerance in the Ottoman Empire. This, in turn, contributed to the emergence of the idea of “universalism” in the works of certain French orientalists, such as Jean Bodin. This was because France was experiencing intense religious conflicts.